Sanatório São Sebastião da Lapa: rupturas e permanências no tratamento da tuberculose (1927-1960) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This work brings us the history of San Sebastian Sanatorium, founded in 1927 and located in the city of Lapa, State of Paraná. For many years it was considered a reference in the treatment of tuberculosis, a disease that in the first half of the 20th century represented, due to its high mortality rates, a major health problem. We will follow how the advances in science and the discovery of new medicines were gradually adopted in the wards of the Sanatorium and how the treatment has changed over time. We will also highlight the definition of the Sanatorium along the lines of a total institution, as defined by Goffman, due to the isolation and control of the inmates. In a second step, we will approach the view that one of its inmates in the 1950s describes us from his letters written in his period of seclusion. My grandfather, Cleto Cardoso, who spent more than two years in treatment at San Sebastian, provides us with his letters with a view from the point of view of the patient and his experience of falling ill. In order to bring this information, we will use, in addition to my grandfather's letters, medical records and reports provided by the Sanatorium, newspapers and interviews with family members.
Keywords: Sanatório São Sebastião; Tuberculose; História das doenças; San Sebastian Sanatorium; Tuberculosis; History of diseases; CNPQ::CIENCIAS HUMANAS::HISTORIA